PERBANDINGAN INTERVENSI MUSCLE ENERGY TECHNIQUE DAN INFRARED DENGAN CONTRACT RELAX STRETCHING DAN INFRARED DALAM PENINGKATAN LINGKUP GERAK SENDI LEHER PADA PEMAIN GAME ONLINE DENGAN MYOFASCIAL PAIN SYNDROME OTOT UPPER TRAPEZIUS DI DENPASAR - Made Aditya Prawira Arthawan; Nila Wahyuni; I Gusti Ayu Artini (Bachelor of Physiotherapy and Physiotherapy Profession Study Program, Faculty of Medicine, Udayana University in collaboration with Indonesian Physiotherapy Association (IPA), 2018)
ABSTRACT Pain is most commonly caused by myofascial pain syndrome, myofascial pain syndrome pain can affect the flexibility of the joints that will cause a decrease range of motion neck joint. The purpose of this study was to determine the comparison between muscle energy technique and infrared with contract relax stretching and infrared in increasing the range of motion neck joint on online game players with myofascial pain syndrome upper trapezius muscle in Denpasar. This research is an experimental research with pre and post test design group control design. The sample is an online game player of 22 people divided into two groups. Group 1 was given intervention of muscle energy technique and infrared, while group 2 was given contract relax stretching and infrared intervention. Result of hypothesis test with paired t-test, group 1 got difference average 6,36 ± 0,62 (p = 0,000) while group 2 got difference mean 5,00 ± 0,357 (p = 0,000). Differential test of improvement after group 1 and group 2 treatment using independent sample t-test showed that group 1 increase was higher than group 2 and this result was significantly different p = 0,019 (p <0,05) Keywords: Range of motion neck joint, myofascial pain syndrome, contract relax stretching, infrared